Effect of service quality, price, and brand image on repurchase intention with customer satisfaction as an intervening variable - Lestari, Pramita; Kurniawan, Bayu; Utami P, Ratih Hesty (PT. Riset Press International, 2024)
This study aims to determine the Influence of Service Quality, Price, and Brand Image on Repurchase Intention with Customer Satisfaction as an intervening variable: A case study at Toko Pantes Ngemplak Pati. This research is conducted using quantitative research, which employs a research instrument in the form of a questionnaire. The sample in this study consisted of 125 respondents. The sample was taken using simple random sampling method, meaning that respondents who became the research sample were encountered by the researcher during the study without considering specific characteristics. The research data were analyzed using Structural Equation Modeling (SEM) statistical method with Amos 23 application. This research already has data that meet validity and reliability tests. This indicates that the data results have met the requirements of the model to proceed to hypothesis testing. The results of this study indicate that: (1) Service Quality does not influence Customer Satisfaction, (2) Price influences Customer Satisfaction, (3) Brand Image influences Customer Satisfaction, (4) Service Quality influences Repurchase Intention, (5) Price influences Repurchase Intention, (6) Brand Image does not influence Repurchase Intention, (7) Customer Satisfaction influences Repurchase Intention.